Análise crítica de metodologia de investigação de áreas contaminadas - avaliação preliminar (AP): um estudo de caso - Silva, Celso Antonio Donizeti da (2017)
Contamination of soils and groundwater by volatile organic compounds promotes numerous environmental and health problems. Soil contaminants are fuel leaks resulting from accidents during transportation or even from inadequate infrastructure in buried tanks. In this context gasoline contamination is the most frequent and results in the contamination by aromatic hydrocarbons (BTEX: Benzene, Toluene, Ethyl-benzene and Xylenes); Such compounds are harmful to human health and the environment. With the expansion of the distribution network in the country and the urban reorganization, a significant increase of areas of contamination risk is observed, especially those already existing. The sample methodologies recommended by the official bodies can be questioned, and during the processes of collection and even execution of the analyzes. As a rule, the applied sampling reduces the collection of soil samples on predetermined length by discrete mathematical modeling. The objective of this work is to propose and analyze the appropriate sampling procedure in order to generate maps of contamination in impacted regions in order to evaluate the initial real size of the contamination detected by BTEX and to propose a sampling procedure that takes into account the Influencing factors such as volatility, soil permeability, temperature and expansion of the contaminated spot among others, in order to allow better evaluation of the soil situation. Soil analyzes obtained in a specific case study in which the presence of BTEX shows a reduction of more than 70% in relation to the methodology certified by CETESB, Gas Chromatography, Mass spectroscopy, The Post in question was evaluated in 5 times and the results Obtained point to contamination in 5 of the occasions the tests are inconclusive because in 3 times they gave negative and others (positive) for BTEX. This reinforces the need to develop more accurate and accurate conceptual models that can actually assure the presence, movement or even storage of the BTEX contaminant